2018
DOI: 10.1111/acem.13634
|View full text |Cite
|
Sign up to set email alerts
|

What Is the Specificity of the Aortic Dissection Detection Risk Score in a Low‐prevalence Population?

Abstract: Background Acute aortic syndrome (AAS) is a time‐sensitive and difficult‐to‐diagnose aortic emergency. The American Heart Association (AHA) proposed the acute aortic dissection detection risk score (ADD‐RS) as a means to reduce miss rate and improve time to diagnosis. Previous validation studies were performed in a high prevalence population of patients. We do not know how the rule will perform in a lower‐prevalence population. This is important because application of a rule with low specificity would increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
0
20
0
1
Order By: Relevance
“…In North American retrospective series of patients undergoing CTA for suspected AAS, the prevalence of AASs was~3%. 8,37 In a vast out-of-hospital study evaluating the ADD-RS in nontraumatic emergencies, the prevalence of AASs was 0.9%. 38 In the studies reviewed herein, the prevalence of AASs was 13% to 23%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In North American retrospective series of patients undergoing CTA for suspected AAS, the prevalence of AASs was~3%. 8,37 In a vast out-of-hospital study evaluating the ADD-RS in nontraumatic emergencies, the prevalence of AASs was 0.9%. 38 In the studies reviewed herein, the prevalence of AASs was 13% to 23%.…”
Section: Discussionmentioning
confidence: 99%
“…First, ADD-RS, a decision rule derived from a retrospective register of AASs, has low specificity. 37 In addition, ADD-RS derivation methods have not been published, and it is currently unknown whether use of the ADD-RS provides any advantage in terms of diagnostic accuracy and of CTA ordering, compared to clinical gestalt. 39,40 In the future, focused ED-centered studies may provide alternative and more specific probability assessment tools.…”
Section: Discussionmentioning
confidence: 99%
“…Even in the only prospective study to date, which did not require the ordering of diagnostic imaging, the prevalence of AAS was 13% . Ohle and colleagues, in this issue of Academic Emergency Medicine, find a somewhat expected result of applying a risk score validated in a high‐prevalence population to a lower‐prevalence population. With a prevalence of AAS of 3.2% in their cohort, they found that the ADD‐RS = 0 had a sensitivity of 100%.…”
mentioning
confidence: 99%
“…Ohle and colleagues rightly bring up a number of concerns about applying this risk score to a low‐prevalence patient population. The low specificity and high sensitivity will result in unacceptably high false‐positive rates, resulting in increased rates of low‐yield, high‐cost diagnostic imaging.…”
mentioning
confidence: 99%
See 1 more Smart Citation